Acculturation, Adaptation, and Mental Health Among Ladakhi College Students: A Mixed Methods Study of an Indigenous Population. (April 2015) - Ozer, Simon
The Indian region of Ladakh has recently undergone comprehensive sociocultural changes through the process of acculturation. The present study employs an acculturation psychological framework to assess how two groups of Ladakhi college students navigate through different degrees of exposure to acculturation and how this affects their mental health. Using mixed methods, 292 (age: M = 20.89, SD = 1.66; 64.4% females) respondents were included in the quantitative assessment and 12 participated in semistructured interviews. Analysis revealed that students with less acculturation exposure were more oriented toward ethnic culture and to a greater extent experienced impaired mental health when compared with the sample with more acculturation. Most prevalent among the students (34.2%) was a bicultural orientation, integrating both ethnic and mainstream culture. In general, acculturation orientation was not associated with quantitative measures of depression or anxiety. The qualitative analysis revealed agency and cultural identity to be pivotal factors in the process of reproducing culture and negotiating cultural change.